UPAYA GURU DALAM MENGINTERNALISASIKAN NILAI-NILAI PANCASILA BAGI SISWA KELAS V SDN 03 BANDAR BUAT KOTA PADANG - Reskiyana Lestari Hasibuan; Atri Waldi; Yesi Anita; Etri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to examine the efforts of teachers in internalizing Pancasila values to fifth-grade students at SDN 03 Bandar Buat, Padang City. The research employs a qualitative descriptive approach with data collection methods including observation, interviews, and documentation. The results show that teachers implement four main efforts: (1) exemplary behavior in daily attitudes and actions, (2) routine habituation activities such as congregational prayers, classroom duties, and reading Juz 'Amma, (3) integration of Pancasila values across all subjects, and (4) individual and collective guidance. The obstacles faced include limited supporting facilities and infrastructure, lack of student awareness in consistently practicing Pancasila values, and external factors such as insufficient parental support and negative peer influences. Solutions implemented include optimizing existing facilities, consistent habituation with positive reinforcement, persuasive and gradual guidance, and intensive communication with parents through parent meetings and class communication groups. The success of internalizing Pancasila values requires continuous collaboration among schools, teachers, students, and parents.